Melamine-phytic acid derived supramolecular synthesis of g-C3N4 for enhanced solar hydrogen evolution. (26th April 2023) - Wang, Bin; He, Huijie; Hao, Hanjing; Li, Peng; Cai, Hairui; Shang, Fanfan; An, Bei; Li, Xiaoqian; Yang, Shengchun
Abstract: It is an effective approach to regulate the structure of photocatalysts by introducing the heteroatoms into the lattice for extended light absorption and enhanced charge separation. In this work, the P atoms were introduced to substitute the corner C atoms of g-C3 N4 by calcinating the melamine-phytic acid derived supramolecular with high-density phosphate groups, which is synthesized by hydrothermal method. The intermediate state produced by the introduction of P atoms leads to the enhanced light absorption of P–CN(7.2g-IP6) with a negative shifted conduction band position, which benefits the photocatalytic hydrogen reaction kinetically. Moreover, the electron transferred from P atom to the surrounding N atoms results in the positively charged P center, which could act as Lewis acid site. Such formed Lewis acid site at positively charged P center together with the Lewis base sites, such as amine or imine groups in P–CN, makes it easier to separate photogenerated charges, thus enabling the P–CN(7.2g-IP6) to exhibit an enhanced photocatalytic hydrogen rate of 2.743 mmol·g −1 ·h −1, which is about 6.77 times that of pristine g-C3 N4 (0.405 mmol·g −1 ·h −1 ). This work provides an alternative approach to regulating the structure of photocatalysts. Highlights: Melamine-Phytic Acid Derived Supramolecular (MP) was obtained by hydrothermal method. P atoms was in situ introduced into g-C3 N4 by calcinating the MP precursor. The P doped g-C3 N4 showed extended absorption and enhanced charge separation. The P doped g-C3 N4 exhibited superior photocatalytic performance than pristine CN.